Urang Banjar Philosophy: Education and The Social Affairs of The Community - Hafidzi , Anwar (LPPPM STAI Darul Hikmah Bangkalan, 2020)
The possibility of social change in the Orang Banjar ideology is illustrated in this study. The people of Banjar demonstrate that farming is to be taught for the next generation, not just for the economies alone Bahuma or right farming. This research is field research with a descriptive-analytical approach. This research found that the philosophics of the traditions of Banjar should thrive wherever they are, with the approach of longitude (honesty, trust and fathanah), superficial (persistent and resilient), tugul (diligent and continuity), paibadah (near to God), batarget (sight and a clear mission). This paper is based on al-Qur'an surah Al-Fath verse 29 and al-A'raaf verse 56 and supports Ashabiyah Ibn Khaldun's theory, which emphasizes that three stages tend to change people's thinking, namely the stage of creation, the stage of enjoyment, and the stage of individuality. Likewise, Arnold Toynbee's theory, which suggests that changes that happen in society, whether they are improvement or failure, can be explained by social concepts that are always interrelated, namely challenges and responses. Keywords: Bahuma, Banjar, society, technology, change, education.